(untitled) (Communications in Computational Chemistry, 2025)
Energy transfer (ET) complex is not rare in bioluminescence. Usually, the ET occurs from the donor with higher emission energy to the acceptor with lower absorption energy. However, a blue-shifted ET is observed in the bioluminescence (BL) of Photobacterium phosphoreum (PP). The luminophore, 4a-hydroxy-5-hydro-flavin mononucleotide at the first singlet excited state (S_1-HFOH), in solitary PP luciferase (PPLuc) emits light at 495 nm. When a proportional concentration of lumazine protein (LumP) with a substrate of 6,7-dimethyl-8-ribityllumazine (DLZ) is introduced, the emission wavelength changes to 475 nm, accompanied by a 2.1-fold enhancement in intensity. The blueshift is only an observation, whose ET mechanism has not been uncovered over fifty years of research. In the present article, we evidenced that the ET process occurs via a Förster resonance energy transfer (FRET) mechanism by protein-protein docking and molecular dynamics (MD) simulations. Moreover, utilizing the combined quantum mechanics and molecular mechanics (QM/MM) method, we calculated the FRET rate and fluorescence quantum yield. The small Stokes shift of DLZ as well as the strong vibronic couplings of HFOH allow the blue-shifted FRET process. The calculated FRET rate is larger than the radiative and non-radiative decay ones of S_1-HFOH, and the fluorescence quantum yield of S_1-DLZ is higher than the one of S_1-HFOH, which clearly explains the experimentally observed enhancement of the emission intensity. Simultaneously, the blue-shifted FRET mechanism firstly interpreted that the wild-type PP emits 475 nm BL rather than 490 nm one as the other species of bioluminescent bacteria do. This first-time deep investigation establishes a theoretical research paradigm for the theoretical study of ET and holds significance in color regulation in the BL field.